Kinematic and mechanical assessment of seated lumbar rotation manipulation: force, velocity and orientation in three dimensions - Han, Changxiao; Chen, Jiali; Gao, Jinghua; Wen, Congcong; Wen, Haibao; Yin, Xunlu; Peng, Bochen; Liu, Guangwei; Zhu, Liguo; Feng, Minshan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundSeated lumbar rotation manipulation is widely used for low back pain, but lacks detailed biomechanical analysis. Understanding its biomechanical characteristics is crucial for therapists to improve comprehension and support education and research. The purpose of this study was to analyze the kinematic and mechanical parameters of Seated lumbar rotation manipulation.MethodsSixty healthy volunteers underwent manipulation by experienced therapists. Three-dimensional movements, thrust velocity, and acceleration were measured using motion capture technology. Force parameters were recorded using pressure sensing gloves mounted on the therapist’s hands. Subgroup comparisons were conducted based on body mass index, and linear regression was used to analyse the relationship between force parameters and BMI (Body Mass Index). Finally, Pearson’s correlation test was employed to examine the correlation between the forces exerted by both hands during each procedure.ResultsKinematic analysis indicated that the angles in three directions were greatest for rotation, followed by lateral bending and flexion. Similarly, rotation was the dominant angular velocities, greater than lateral flexion and anteflexion. Furthermore, Preload duration (2.72 ± 0.10 s) and thrust duration (0.48 ± 0.04 s) were recorded. In terms of force, four key force metrics were calculated: preload force (58.99 ± 9.76 N), valley force (23.25 ± 6.24 N), thrust force (50.54 ± 9.63 N), and peak force (73.77 ± 11.06 N). While the preload rate (21.73 ± 4.66 N/s), thrust rate (106.30 ± 11.72 N/s), and the maximum torque (51.86 ± 7.52 N m) were determined. Subgroup analysis showed significant differences in force parameters by body types (P < 0.01). Linear regression revealed a positive correlation between BMI and force parameters (P < 0.05), and Pearson analysis indicated a significant correlation between forces exerted by both hands (P < 0.05).ConclusionSeated lumbar rotation manipulation is characterized by long-lever, three-dimensional coupled movements with high-velocity, low-amplitude thrusts. Additionally, the force parameters are positively influenced by somatotype, and bilateral hand force exerts a synergistic effect. This valuable biomechanical quantification help comprehending the technique and supporting its educational and experimental settings.